Correction: Rhus verniciflua as a green corrosion inhibitor for mild steel in 1 M H2SO4. Issue 96 (30th September 2016) - Prabakaran, Mayakrishnan; Kim, Seung-Hyun; Hemapriya, Venkatesan; Gopiraman, Mayakrishnan; Kim, Ick Soo; Chung, Ill-Min
Abstract : Correction for ' Rhus verniciflua as a green corrosion inhibitor for mild steel in 1 M H2 SO4 ' by Mayakrishnan Prabakaran et al., RSC Adv., 2016, 6, 57144–57153.